Mastery Ability of Chinese Proverbs in Mandarin Language Education Study Program Students - Belinda Vashti; Lily Thamrin; Tjen Veronica (Jurnal Mantik, 2022)
This is a study that related to the Mandarin Language proverb which aims to determine the mastery ability and difficulty in using Mandarin Language proverbs for Language Education and Art Major in Mandarin Education Language Study Program students batch of 2018 FKIP Tanjungpura University. This research is a qualitative research with the total 33 students as respondents. The data in this study were the results of answering the questions test and questionnaires about Mandarin Language proverbs. The methods of data analysis were using mixed research methods. The research results showed that the mastery ability of Language Education and Art Major in Mandarin Education Language Study Program students batch of 2018 FKIP Tanjungpura University against the Mandarin Language proverbs were poor, with an average of 52.78%. This showed that they still did not enough understand about the Mandarin Language proverbs that has been learned. The factors causing the difficulty of using the Mandarin Language proverbs were lack of basic knowledge, not enough of reading and lack of practice.